If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5n + 1) = 12 Reorder the terms: -2(1 + 5n) = 12 (1 * -2 + 5n * -2) = 12 (-2 + -10n) = 12 Solving -2 + -10n = 12 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -10n = 12 + 2 Combine like terms: -2 + 2 = 0 0 + -10n = 12 + 2 -10n = 12 + 2 Combine like terms: 12 + 2 = 14 -10n = 14 Divide each side by '-10'. n = -1.4 Simplifying n = -1.4
| 4(0.35-x)=x-7 | | [9-5(x-2y)]+9(2x+y)= | | -4(3+x)=-32 | | x^3+6x^2+12x-56=0 | | 2x^2+2x-2=14 | | 132-6x=3x+6 | | 2x^2+2x-1= | | 2x^2=2x-1 | | 2b+9(2-4)= | | fx=x^2-x-2 | | 3x+8+x=180 | | 10=26-2.5x | | d=200t | | 8(c-3d)-(4c+d)= | | 6m^2-13m+6=0 | | 69-(4x+16)=4(x+2)+x | | 6(5x-2)X=108 | | 5(2z-1)-5(2+5)=3(2+1) | | 6m^2-13m+5=0 | | 15m^2-34m+15=0 | | 2.8x=22.4 | | 5+x=26 | | x+3/5=5 | | 4a^2+12a=0 | | 3(x+5)=-1(2x) | | 10x=5x | | x+5(3)=-1(2x) | | 2=3(x-4) | | x/9=4 | | 2x^2-3x+19=0 | | q^2+15q+56=0 | | 8a^2-16a+6= |